2016
DOI: 10.3389/fpls.2016.01405
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plant-Growth-Promoting Fungi Trichoderma longibrachiatum T6 Enhances Tolerance of Wheat to Salt Stress through Improvement of Antioxidative Defense System and Gene Expression

Abstract: Soil salinity is a serious problem worldwide that reduces agricultural productivity. Trichoderma longibrachiatum T6 (T6) has been shown to promote wheat growth and induce plant resistance to parasitic nematodes, but whether the plant-growth-promoting fungi T6 can enhance plant tolerance to salt stress is unknown. Here, we determined the effect of plant-growth-promoting fungi T6 on wheat seedlings’ growth and development under salt stress, and investigated the role of T6 in inducing the resistance to NaCl stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
133
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 73 publications
18
133
0
1
Order By: Relevance
“…However, an increase in the speed of symptom appearance and internal stem necrosis was found in P. radiata inoculated with T. viride prior to challenge with F. circinatum , and several parameters were influenced either by amplifying its response (lower water potential and A , higher C i ) or by revealing novel responses not reported in plants inoculated exclusively with F. circinatum (decrease in RWC, increase in EL and SA concentration). Moreover, although P. radiata RWC increased upon T. viride inoculation, as verified in wheat in the presence of Trichoderma longibrachiatum (Zhang et al , ), when both fungi co‐occurred a reverse response was found.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, an increase in the speed of symptom appearance and internal stem necrosis was found in P. radiata inoculated with T. viride prior to challenge with F. circinatum , and several parameters were influenced either by amplifying its response (lower water potential and A , higher C i ) or by revealing novel responses not reported in plants inoculated exclusively with F. circinatum (decrease in RWC, increase in EL and SA concentration). Moreover, although P. radiata RWC increased upon T. viride inoculation, as verified in wheat in the presence of Trichoderma longibrachiatum (Zhang et al , ), when both fungi co‐occurred a reverse response was found.…”
Section: Discussionmentioning
confidence: 79%
“…Based on the literature, either a beneficial or neutral effect of Trichoderma on Pinus response against F. circinatum would be expected (reviewed by Mart ın-Garc ıa et al, 2019). However, an increase in the speed of symptom appearance and internal stem necrosis was found in P. radiata inoculated with T. viride prior to challenge with F. circinatum, and several parameters were influenced either by amplifying its response (lower water potential and A, higher C i ) or by revealing novel (Zhang et al, 2016), when both fungi co-occurred a reverse response was found. Although Shemakhanova (1962) reported that T. viride may reduce mycorrhiza formation and seedling growth in woody plants, the time elapsed between T. viride and F. circinatum inoculations in the present study (2 weeks) seems too short to shift the plant natural microbiome and suppress immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple superphosphate, a readily available source in the soil, presented the most promising result because the analysis was performed twenty days after the planting of the crop, a result that was already expected. Some authors have demonstrated the increase on chlorophyll level due the presence of Trichoderma on different cultures as cucumber, wheat, soybean and lettuce plants [59][60][61][62] .…”
Section: Discussionmentioning
confidence: 99%
“…Then, ddH 2 O was added to the samples until the extract solutions reached a final volume of 100 mL for grape berries and 10 mL for A. thaliana leaves. Measurements were performed as previously described with some modifications [54,55]. A 0.5 mL aliquot of extract solution was mixed with 5 mL of 4% anthrone solution (dissolved in 88% concentrated sulfuric acid) and incubated in a 90 • C water bath for 15 min.…”
Section: Soluble Sugar Measurementsmentioning
confidence: 99%